Third Spaces, Religion and Spirituality in the Digital Age Panel 2 - Echchaibi, Nabil; Stadlbauer, Susanne; Rajabi, Samira; Evolvi, Giulia; Kim, Seung Soo (AoIR Selected Papers of Internet Research, 2013)
How can we study religion and spirituality in the digital age without privileging the techno-fantastic or reifying deterministic binaries of old media-old religion versus new media-new religion? Framing our research around the novelty of technologies leads us to adopt a hierarchical indexing of what constitutes a real, authentic experience of community, belonging and belief, precisely because we draw distinct lines between the traditional and the modern, the physical and the digital, place and non-place, and the real and the proximal embodied experience. As Hermann Bausinger argues, folk culture and tradition are much alive in the world of modern technologies and “busily recruiting and adapting new technologies to old purposes.” If mediation is an inherent function of religion and if we agree that new media are not just technological innovations but continuous cultural and social spaces (Moores, 2012), what’s new in digital religion and how and where can we locate differences and disjunctures in the religious today without reducing newness to simply leaving tradition behind?This panel argues that our theories of religion and the media will benefit greatly from an analysis of how religious meaning is generated and performed at the borderlines of a complex ecosystem of media ensembles and hybrid spaces. Religion is not simply the subject of yet another round of media technologies. The articulation and contestation of what constitutes the religious increasingly take place in in-between spaces where we move beyond narratives of origin and hierarchical subjectivities. Our appropriation of the concept of Third Spaces serves as an interpretive tool to highlight what we call a ‘thickening’ of the religious experience beyond dichotomous definitions of both religion and media categories. In this sense, and rather than treating the digital as having a “self-enclosed cyberian apartness” (Miller and Slater, 2000), we privilege an understanding of religious and spiritual practices in the digital as part of everyday life and the outcome of potentially contested sites. The spatial metaphor of a third space also allows us to visualize the mobility of everyday religion and explore the dynamic ways in which contemporary subjects imagine, produce and navigate new religious and spiritual places.The digital in a third space configuration also becomes much more revealing because it makes legible the dynamics of translation and reflexivity as individuals, and at times institutions too, seek alternative modes of belonging and community building. So, instead of seeing the digital in the study of religion solely in terms of its technical properties and their impact on some pure belief or on the authenticity of the spiritual experience, we look at it as a complex text of social practice, a site of negotiated religious praxis, which resists totalizing and monologic frames of reference and produces its own spiritual repertoire, its own discursive logic, and its own aesthetics of persuasion.Digital third spaces of religion thus stand out by virtue of their in-betweenness. They exist between private and public, between institution and individual, between authority and individual autonomy, between large media framings and individual "pro-sumption," between local and translocal, etc. Our empirical case studies reflect on the creative outcomes of this condition of in-betweenness and the emergence of other places of religious and spiritual meaning, particularly as intervening sites of social practice, or even peripheral spaces of power negotiation and social action. These third spaces of digital religion, we contend, can be strategically peripheral as they imagine creative ways of thinking about faith and spirituality while resisting entrenched frames of social power and nested structures of religious authority. Highlighting the contestatory potential of these sites, however, is not meant to endorse a rampant view of digital utopianism or obscure the fact that digital cultures still operate within a logic of neoliberalism. Rather, we believe that a critical analysis of these spaces can elicit an important contemporary dynamic of religious practice and change and assess the work of social actors who act meaningfully in and through these spaces as viable sites of cultural intervention and imagination of alternative possibilities.This panel will present findings from a two-year research project entitled,‘Finding Religion in the Media”, in which a group of researchers surveyed and analyzed media spaces where the terms and practices of religion, spirituality, the ‘not-so-religious’ and the not-so-spiritual,’ and things that bear a resemblance to religion, are present. Drawing on the philosophy of technology, religious studies, media studies, and postcolonialism, this panel examines alternative ways in which we can think about the intimate nexus between the religious and the mediated in the age of the digital.